Combined method of detecting network attacks based on the analysis and identification of abnormal network conditions - Данилина, Г. В.; Милокум, Я. В. (Problems of Informatization and Control, 2008)
We propose a combined method of detecting network attacks , based on the analysis of signatures , protocols, and static methods of detection and recognition . The technique of co- signature-based Intrusion Detection and statistical methods